Exploitation of Bush Mango (Irvingia wombolu and Irvingia gabonensis) Among Rural Household in Enugu State, Nigeria - J M Chah; N A Ani; J I Irohibe; A E Agwu (Journal of Agricultural Extension, 2012)
The study was undertaken to assess the exploitation of Bush Mango Irvingia gabonensis and Irvingia wombolu (ogbono) among rural households in Enugu State, Nigeria. Interview schedule was used to collect data from 91 respondents and data were analyzed by use of descriptive statistics and factor analysis. The mean age of the respondents was 42 years, majority (56%) were male and about 54% married. The mean household size and monthly income of respondents was 6 persons and N15, 970 respectively. About 12% had no formal education.. Majority (87.9%) of the respondents had no access to extension services and credit facilities (74.7%). The major system (89%) of exploiting Irvingia gabonensis and Irvingia wombolu is from the wild. Other exploitation systems were: around homestead (85.7%), agroforestry (83.5%), and Irvingia plantations (39.6%). The major benefits of Irvingia products include: condiment/soup thickener (M= 2.80), source of income (M= 2.77), fruit as food (M= 2.63), firewood (M= 2.40), among others. The constraints to exploitation of Irvingia were identified and factorized into production constraints, economic constraints and technological/institutional constraints. Farmers should be educated by extension on how to limit these constraining factors and the need to domesticate Irvingia and appropriate technologies should be transferred to the farmers as this will go a long way to increase productivity.